Impact of modulating leptin sensitivity on the transcriptomic profile of adult-derived hypothalamic mouse neurons - Ocłoń, Ewa; Gurgul, Artur; Szmatoła, Tomasz; Jasielczuk, Igor; Kucharski, Miroslaw; Zubel-Łojek, Joanna; Zieba, Dorota Anna (Frontiers in Molecular Neuroscience, 2025)
The modulation of leptin sensitivity in hypothalamic neurons plays a crucial role in metabolic regulation and the development of obesity. Three distinct approaches, exposure to leptin (LEPA), administration of leptin antagonist (LANTA), and treatment with palmitate (PA), were explored in this study to assess their effects on adult-derived mHypoA-2/12 neurons and the resulting transcriptomic signatures. To this end, 3’ mRNA-Seq transcriptome analysis was employed, unexpectedly revealing downregulation of key genes associated with the NOD-like receptor signaling pathway (Irf9, Mapk3, Stat2, Nfkbia, Ikbkg, Rela, Cxcl1, and Traf5), the C-type lectin receptor signaling pathway (Nfkb2, Irf9, Mapk3, Stat2, Nfkbia, Ikbkg, Rela, and Ptgs2), the NF kappa B signaling pathway (Nfkbia, Ikbkg, Nfkb2, Rela, Traf5, Cxcl1, and Ptgs2), and the IL 17 signaling pathway (Nfkbia, Ikbkg, Mapk3, Rela, Traf5, Cxcl1, and Ptgs2). These findings help elucidate the molecular mechanisms through which these factors influence leptin sensitivity and provide insights into the pathways implicated in the development of leptin resistance in hypothalamic neurons. The surprising downregulation of these pathways suggests a complex interplay between leptin signaling and the cellular stress response in hypothalamic neurons. This alteration may reflect adaptive mechanisms in response to prolonged leptin or fatty acid exposure. Understanding these dynamics is essential for elucidating the role of hypothalamic inflammation in the progression of leptin resistance and associated metabolic disorders.